The Effect of Operational Complexity,Business Risk, and Audit Committee on Audit Quality with Audit Delay as Modderation - Evita Bintang Timur; David Pangaribuan; Uswatun Khazanah; Agnes Mariana Pardosi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effect of operational complexity, business risk (leverage) and audit committee on audit quality with audit delay as a moderating variable. The research method uses a quantitative method with the object of research being banking companies for the period 2019-2023. Data sources from the Indonesian Stock Exchange. The results of the study concluded that (a) Operational complexity has a positive effect on audit quality (b) Business risk (Leverage) has an effect on audit quality (c) The audit committee has a positive effect on audit quality (d) Audit delay cannot moderate the effect of operational complexity on audit quality (e) Adit delay cannot moderate the effect of company risk on audit quality and (f) Audit delay can moderate the effect of the audit committee on audit quality, meaning that audit delay weakens the positive effect of the audit committee on audit quality. The results of this study have positive implications for regulators, investors, the government and prospective investors as well as public accounting firms. Public trust in the implementation of transactions on the Stock Exchange is an important indicator to encourage national economic growth, therefore audit quality is the key to maintaining trust in companies that present financial reports, investors and prospective investors in making investment decisions, public accounting firms as audit implementers